Parent-implemented early intervention design for improving speech and language skills among Mandarin-speaking infants and toddlers with cleft lip and/or palate - Sha Lai; Li Lu; Zhongliang Zhou; Chi Shen; Binting Yang; Binting Yang; Zhanping Ren; Zhanping Ren; Siwei Ma; Siwei Ma; Siwei Ma (Frontiers in Public Health)
BackgroundCleft lip and/or palate (CL/P) speech is a significant communication disorder with notable and enduring consequences. This study focused on developing an intervention mapping (IM)-based and parent-implemented early intervention to improve speech and language skills among infants and toddlers with CL/P in China.MethodsAn IM procedure was used to develop a parent-implemented early intervention. First, parent–child interaction problems affecting language development in infants and toddlers were identified through 132 questionnaires completed by parents of children with CL/P and 30 family videos of parent–child interactions. Second, according to the problem diagnosis, the logical model of parent–child interaction behavior change was constructed. Finally, the health outcomes were transformed into intervention goals at three levels (i.e., infants and toddlers with CL/P, parents and environment), and a set of early intervention programs were designed by integrating various intervention techniques.ResultsThe diagnosis of parent–child interaction problems showed that 40.91% of parents and children often use electronic media together; in parent–child interaction, 41.67% of parents presented ‘lack of waiting’, 29.55% overcorrected pronunciation errors. Video analysis revealed issues in parent–child interaction, such as inadequate parental skills, ineffective interactions, and an unsuitable environment. A parent-implemented early intervention was developed, including the following specific steps: health education within the hospital, 9 days of an online reading program in WeChat groups, face-to-face standardized training workshops, and individualized video feedback therapy.ConclusionWe have devised a parent-implemented early intervention to enhance speech and language abilities in Mandarin-speaking infants and toddlers with CL/P, overcoming the shortage of speech therapy services in China.